MARKETING MANAGEMENT OF AGRICULTURAL BUSINESS: CHALLENGES OF DIGITALIZATION - KORIUHIN, Andrii; MATVEYEV, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the impact of digitalization processes on the agricultural sector and the challenges faced by enterprises in this industry. The author analyzes the impact of external and internal environmental factors on the development of agricultural businesses and the problems that delay the development of digital technologies in agriculture. It is noted that an important element of marketing management is a systematic approach that allows establishing relationships between these factors, assessing their impact and formulating marketing management strategies. Based on the results of the study, the author substantiates the need to create favorable conditions for the introduction of digital tools in the marketing management of agricultural businesses. The results of the analysis also indicate the potential of using innovative marketing methods, such as analyzing market trends and using digital communication channels, to overcome the challenges of digitalization and increase the competitiveness of the agricultural sector. The prospects for the development of digitalization processes in the marketing management of agricultural enterprises are considered. It is noted that through systematic market analysis, budget management, and the use of digital technologies and communication channels, enterprises can skillfully navigate market fluctuations while optimizing operational resources. The study provides the conclusions necessary for the further development of marketing management strategies in agriculture, taking into account the current challenges of digitalization and the needs of agricultural businesses in Ukraine. It is stated that the prospects for the development of digitalization processes in agrarian business emphasize the importance of integrating marketing management into the strategic planning of agricultural enterprises and its potential to increase the efficiency of innovation in this sector.
Keywords: marketing management; agricultural business; agriculture; digitalization; digital transformation; innovation